Characteristics of Economic Performance in former Soviet Countries: Lessons Learned from Last Two Decades - Yormirzoev, Mirzobobo; Yormirzoeva, Firuza; Gorodilov, Aleksei (Economy of Regions, 2020)
This paper attempts to explore economic performance in countries of the former Soviet Union since their transition to a market system based on the World Bank data for the period from 1993 to 2016. The first part of the study is related to estimating proximate sources of economic growth within the standard growth accounting framework. Results indicate that under the period of study capital accumulation was the primary engine for growth in the post-Soviet region. Total factor productivity (TFP) growth rates were modest ranging from 1.15 % for Uzbekistan and 0.77 % for Belarus to -1.83 % for Turkmenistan and -1.20 % for Latvia accordingly. In the second part of the paper we analyse productivity level across all former Soviet republics by decomposing differences in output per worker into differences in capital intensity and productivity for the year 2016. Compared to Russia, a frontier for the analysis, nearly all former Soviet republics demonstrated a lower level of productivity. Some countries of the region such as Georgia, Kyrgyz Republic and Turkmenistan have extremely high capital intensity. Productivity in Russia was about 14 times higher than productivity in Kyrgyz Republic and Tajikistan. Despite the fact that more than two decades passed since the transition to a market system the Soviet legacy of aggregate production did not experience notable changes.